2018
DOI: 10.1002/14651858.cd011809.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Application of seminal plasma to female genital tract prior to embryo transfer in assisted reproductive technology cycles (IVF, ICSI and frozen embryo transfer)

Abstract: We included 11 RCTs (3215 women). The quality of the evidence ranged from very low to low. The main limitations were risk of bias (associated with poor reporting of allocation concealment and other methods) and imprecision for the primary outcome of live birth rate.Live birth rates: There was insufficient evidence to determine whether there was a difference between the groups with respect to live birth rates (RR 1.10, 95% CI 0.86 to 1.43; participants = 948; studies = 3; I = 0%). Low quality evidence suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Future perspectives in the treatment of RPL of immune etiology could be aimed to correct abnormal decidualization as well as dysfunctions of the immune mechanisms occurring in the endometrium and decidua, on the basis of the emerging evidence. As an example, the effects of seminal plasma on the expansion of Tregs could allow an innovative therapeutic approach, that is already being used in assisted reproductive technologies (ART), even though with still controversial results [196][197][198]. Table 6.…”
Section: Discussionmentioning
confidence: 99%
“…Future perspectives in the treatment of RPL of immune etiology could be aimed to correct abnormal decidualization as well as dysfunctions of the immune mechanisms occurring in the endometrium and decidua, on the basis of the emerging evidence. As an example, the effects of seminal plasma on the expansion of Tregs could allow an innovative therapeutic approach, that is already being used in assisted reproductive technologies (ART), even though with still controversial results [196][197][198]. Table 6.…”
Section: Discussionmentioning
confidence: 99%
“…The Cochrane review that compiled these RCTs concluded that there was no clear evidence of a difference in LBR with seminal plasma application or exposure (RR 1.10; 95% CI, 0.86-1.43; 3 RCTs, n ¼ 948) (17). There was an improvement in clinical pregnancy rates noted with seminal plasma application (RR 1.15; 95% CI, 1.01-1.31; 10 RCTs, n ¼ 2768), but when the analysis was restricted to studies at low risk of bias this difference was no longer present (RR 1.06; 95% CI, 0.81-1.39; 3 RCTs, n ¼ 547).…”
Section: Seminal Plasmamentioning
confidence: 99%
“…However, transformed offspring phenotype was ascribed to sperm damage and absence of seminal fluid [ 136 ]. It is evident that seminal plasma and sperm-borne mediators are critical for signaling events that lead to successful pregnancy and healthy offspring; however, there are differences across species [ 119 , 127 , 137 ] that raise the question of whether seminal plasma is a prerequisite in cattle breeding. It should be noted that the interaction of hub genes of DE-miRNAs in the PPI network was found in this current study.…”
Section: Discussionmentioning
confidence: 99%